Diferencias culturales - Principe Trujillo, Bettel Amaliz (2020)
In this work of professional proficiency, the topic of "Cultural Differences" will be addressed, which is designed for students in the third grade of secondary school. It consists of three chapters, in the first one is the design of the learning session in which diverse didactic strategies have been used in order to achieve that the students are interested and understand the knowledge that is offered to them. In the second chapter, I present the scientific-theoretical support of the topic I have approached, making use of bibliographical sources of diverse authors. And finally, in the third chapter, I present the pedagogical support where sources of the Ministry of Education have been used and revised, such as the National Education Curriculum, the National Curriculum Design, among others. At the same time, I have complemented the work with my own knowledge that I have been able to acquire during my years of study. The competence that is developed in this session is Live and participate democratically in the search for the common good, the capacity; participate in actions that promote the common welfare, the performance; exchange cultural practices in relation to lifestyles showing respect for differences and purpose, make informative posters where they recognize the importance of cultural differences. The purpose of this work is for students to understand what cultural differences are, and to identify them, thus recognizing the importance they have in society, since it is a formative topic in itself that will be served throughout their lives because it is part of their social reality.